Use of on-line liquid chromatography-nuclear magnetic resonance spectroscopy for the rapid investigation of flavonoids from Sorocea bomplandii - Andrade, FDP; Santos, L. C.; Datchler, M.; Albert, K.; Vilegas, Wagner [UNESP] (Elsevier B.V., 2002)
This paper reports the identification of di- and triglycosylated flavonoids from Sorocea bomplandii (Moraceae) by liquid chromatography coupled on-line to nuclear magnetic resonance (LC-NMR). These glycosylated flavonoids may be used as a taxonomic marker in future work. (C) 2002 Elsevier B.V. B.V All rights reserved.
Keywords: Sorocea bumplandii; nuclear magnetic resonanc spectroscopy; flavonoids